Islam and Gender Consciousness: Analysis and Application in Contemporary Society - Zulpandri; Ronaldi; Rusydi, AM; Sri Wahyuni; Mowafg Masuwd (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This article aims to analyze the concept of gender consciousness from an Islamic perspective and its relevance in contemporary society. This study focuses on the principles of justice, spiritual equality, and complementary gender roles. The ultimate goal is to formulate a moderate, contextual, and applicable framework for Islamic gender consciousness. Theoretical framework: This research uses the framework of Islamic justice and spiritual equality. The analysis is supported by maqashid al shariah and the thought of contemporary scholars. This framework emphasizes the balance of gender rights and responsibilities. Literature review: Previous studies have shown diverse views on Islam and gender. Gender inequality is often associated with patriarchal culture and interpretations. However, contextual synthesis studies are still limited. Methods: This study uses a qualitative approach based on literature studies. Data are obtained from the Quran, Hadith, and the latest academic literature. The analysis is carried out through content and thematic analysis. Results: The results of the study show that Islamic gender awareness is based on proportional justice, not absolute equality. Gender inequality in social practice is more influenced by cultural factors and ahistorical interpretations. Moderate Islamic gender awareness has proven to be relevant for maintaining social balance and harmony in society. Implications: These findings have implications for strengthening education and gender-fair policies. Islamic gender awareness can prevent discrimination and extremism. This approach supports social harmony. Novelty: The novelty of this research lies in the synthesis of Islamic values and modern gender issues. This article offers a moderate Islamic gender awareness concept. This approach is both applicable and contextual.